West African Popular Theatre - Barber, Karin, 1949- (Book collections on Project MUSE., 1997)
" ... A ground-breaking contribution to the field of African literature ..." 'Research in African Literatures "Anyone with the slightest interest in West African cultures, performance or theatre should immediately rush out and buy this book." 'Leeds African Studies Bulletin "A seminal contribution to the fields of performance studies, cultural studies, and popular culture." 'Margaret Drewal "A fine book. The play texts are treasures." 'Richard Bauman African popular culture is an arena where the tensions and transformations of colonial and post-colonial society are played out, offering us a glimpse of the view from below in Africa. This book offers a comparative overview of the history, social context, and style of three major West African popular theatre genres: the concert party of Ghana, the concert party of Togo, and the traveling popular theatre of western Nigeria